The Role Of Bali Cultural Values Under Development Social Child Age Early - I Made Hartawan; Tjipto Sumadi; Yuliani Nurani3 (Exploration in Early Childhood Research, 2024)
This study aims to determine the role of Balinese cultural values on social development of early childhood. The Balinese cultural values focused on in this research are the tri kaya parisudha values. The tri kaya parisudha value consists of thinking (manacika), saying (wacika) and doing (kayika) good and right. The research method used is qualitative research. Technique collection data use observation, interview. The data analysis technique used is Miles and Huberman. The research findings show the role of the tri kaya parisudha value in activities Which it's been planned by the teacher good inside or outside class. This activity is able to develop the social skills of children aged 5-6 years, such as saying good and correct greetings, children acting as fathers, mothers, brothers and sisters and discussion activities carried out by teachers. The conclusion of this research is that social development will develop well if the role of the tri kaya parisudha value is optimized in children's play activities. Children need to be equipped with cultural values, especially the tri kaya parisudha values, so that they are able to socialize in their environment.